Nurse's new year with the billionaire - Baine, Karin (Harlequin medical romance., 2024)
Nurse Jo is facing the New Year with nothing; no boyfriend, no business, no home. So when she's offered a role caring for the matriarch of an obscenely wealthy family - on a private island! - it's just the escape she needs. Being tempted by her patient's outrageously attractive grandson is not! Billionaire Dr Taylor doesn't trust easily, and Jo is no exception. Yet, as they work together, mutual respect and desire blossoms, quickly leading to a steamy fling. But when the clock strikes midnight, will the fireworks between them fizzle out as planned... or flame brighter than ever?